2022
DOI: 10.3389/fpsyg.2022.872061
|View full text |Cite
|
Sign up to set email alerts
|

Learning from feedback: Evaluation of dynamic decision-making in virtual reality under various repetitive training frameworks

Abstract: Dynamic decision-making involves a series of interconnected interdependent confluence of decisions to be made. Experiential training is preferred over traditional methods to train individuals in dynamic decision-making. Imparting experiential training in physical settings can be very expensive and unreliable. In virtual reality (VR), synthetic environments play a significant role in providing flexible and cost-effective training environments to enhance dynamic decision-making. However, it is still unclear how … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…These results concurred with the work done by researchers in [28], who reasoned that due to the ability of vibrotactile feedback and 360° locomotion's ability to engage the proprioceptive senses, it manages to capture a participant's attention and exacerbates the sense of "being there" in the serious simulation, eventually managing to create a coherent and compelling perceptual experience. Researchers in [26] also reasoned that multisensory feedback was linked to embodied presence, i.e., the feeling of control and influence over the virtual actions being executed by the participants. A qualitative, formal interview with the participants in the experimental condition also revealed that positive emotional responses and excitement also contributed to a sense of immersion and presence, even though it did not translate into higher performance satisfaction.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These results concurred with the work done by researchers in [28], who reasoned that due to the ability of vibrotactile feedback and 360° locomotion's ability to engage the proprioceptive senses, it manages to capture a participant's attention and exacerbates the sense of "being there" in the serious simulation, eventually managing to create a coherent and compelling perceptual experience. Researchers in [26] also reasoned that multisensory feedback was linked to embodied presence, i.e., the feeling of control and influence over the virtual actions being executed by the participants. A qualitative, formal interview with the participants in the experimental condition also revealed that positive emotional responses and excitement also contributed to a sense of immersion and presence, even though it did not translate into higher performance satisfaction.…”
Section: Discussionmentioning
confidence: 99%
“…Like haptic feedback systems, 360° locomotion treadmills signify a notable progression in virtual reality interaction, facilitating users to engage in naturalistic movement within virtual spaces [25]. In contrast to traditional VR setups that rely on handheld controllers for locomotion, these treadmills allow users to walk, run, turn, and navigate freely in all directions, enabling unrestricted movement [25][26][27]. The ability to move freely and interact with virtual spaces as they would in the physical world eliminates the disconnect between motor actions and visual feedback, reducing motion sickness and enhancing spatial presence [27].…”
Section: Introductionmentioning
confidence: 99%